Predicting Responses to Psychedelics: A Prospective Study - Haijen, Eline C. H. M.; Kaelen, Mendel; Roseman, Leor; Timmermann, Christopher; Kettner, Hannes; Russ, Suzanne; Nutt, David; Daws, Richard E.; Hampshire, Adam D. G.; Lorenz, Romy; Carhart-Harris, Robin L. (Frontiers in Pharmacology, 2018)
Responses to psychedelics are notoriously difficult to predict, yet significant work is currently underway to assess their therapeutic potential and the level of interest in psychedelics among the general public appears to be increasing. We aimed to collect prospective data in order to improve our ability to predict acute- and longer-term responses to psychedelics. Individuals who planned to take a psychedelic through their own initiative participated in an online survey (www.psychedelicsurvey.com). Traits and variables relating to set, setting and the acute psychedelic experience were measured at five different time points before and after the experience. Principle component and regression methods were used to analyse the data. Sample sizes for the five time points included N= 654, N= 535, N= 379, N= 315, and N= 212 respectively. Psychological well-being was increased two weeks after a psychedelic experience and remained at this level after four weeks. This increase was larger for individuals who scored higher for a ‘mystical-type experience’, and smaller for those who scored higher for ‘challenging experience’. Having ‘clear intentions’ for the experience was conducive to mystical-type experiences. Having a positive ‘set’, as well as having the experience with intentions related to ‘recreation’, were both found to decrease the likelihood of having a challenging experience. The trait ‘absorption’ and higher drug doses promoted both mystical-type and challenging experiences. When comparing different types of variables, traits variables seemed to explain most variance in the change in well-being after a psychedelic experience. These results confirm the importance of extra-pharmacological factors in determining responses to a psychedelic. We view this study as an early step towards the development of empirical guidelines that can evolve and improve iteratively with the ultimate purpose of guiding crucial clinical decisions about whether, when, where and how to dose with a psychedelic, thus helping to reduce risks while maximising potential benefits in an evidence-based manner.